Front Cover: Luminescent Coordination Polymers Constructed from a Flexible, Tetradentate Diisopyrazole Ligand and Copper(I) Halides (Chem. Asian J. 5/2020). Issue 5 (30th January 2020) - Yoneda, Tomoki; Kasai, Chika; Manabe, Yumehiro; Tsurui, Makoto; Kitagawa, Yuichi; Hasegawa, Yasuchika; Sarkar, Parantap; Inokuma, Yasuhide
Abstract : An ethylene‐bridged diisopyrazole ligand forms one‐ and two‐dimensional luminescent coordination polymers through complexation with Cu(I) halides. While chloride and bromide form infinite coordination chains with trigonal planar copper(I) coordination geometry, iodide results in the formation of a coordination network with stair‐step type Cu4 I4 subunits that exhibits thermochromic emission. These results illustrate the inherent structural flexibility of the diisopyrazole ligand to adopt both planar and stepped conformations in the solid state. More information can be found in the Full Paper by Yasuhide Inokuma et al. on page 601 in Issue 5, 2020 (DOI: 10.1002/asia.201901682 ).